An Analysis of Factors Affecting the Growth of The Non-Star Hotel Tourism Sector in North Kalimantan - Renta Yustie; Novi theresia kiak; Clarce S. Maak; Yonas Ferdinand Riwu (Universitas 17 Agustus 1945 Surabaya, 2026)
The tourism sector plays an important role in driving regional economic growth in North Kalimantan by absorbing labor and attracting both domestic and international tourists, which contributes to the Gross Regional Domestic Product (GRDP) of the accommodation and food and beverage sub-sector. Tourism development is supported by the availability of restaurants, accommodation facilities, and bedrooms, which act as key drivers of tourism activities, particularly in the non-star hotel sector. This study aims to analyze the factors influencing the growth of non-star hotel tourism in North Kalimantan. The GRDP of the accommodation and food and beverage sub-sector is used as the dependent variable to represent sector growth, while the number of restaurants, accommodation establishments, and bedrooms serve as independent variables. The study covers the period from 2018 to 2023 across five districts/cities: Malinau, Bulungan, Tana Tidung, Nunukan, and Tarakan. Panel data regression analysis is applied using CEM, FEM, and REM models. The results indicate that restaurants, accommodation, and bedrooms have a significant positive effect on the growth of the non-star hotel tourism sector.